(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
دراسة في التصوف الحضاري العربي الإسلامي منذ إرهاصاته الأولى على مدى القرنين الأول والثاني الهجريين وصولاً إلى نضج هذه المعرفة بدءاً من نهاية القرن الثاني الهجري وعلى امتداد العصرين العباسيين الأول والثاني ، أي حتّى بدايات القرن الخامس الهجري ، متفتحة مذاهب ومدارس عرضنا لها وبمفاتيحها الاصطلاحية التي تحدّت قيماً دينية رسمية وبخاصة : التوحيد والنبوة والإنسان ، إلى أن خلصنا إلى موقف وتقييم لهذه المعرفة الديمقراطية مقابل وبالتعارض الإيديولوجي والمعرفة مع كل معرفة استبدادية مغلقة . This piece of research present a study of the Arabic and Islamic civilized Sufism since its early stages spanning over the first two Hijra centuries up until the ripe period of this domain starting from the end of the second Hijra century and over the two Appaseid centuries ( the first and the second). That is, this last till the beginning of the fifth Hijra century, however, this creates a few approaches and schools that this research highlights together with their relevant terms that violates certain religion values: monotheism, prophesy and the man. This research conclude with a stand toward assessing this democratic awareness against the ideology of each egoistic filed of knowledge.